The Effect of MVA, ROE, and NPM on The Return of Indonesian Sharia Stock Index 2019-2023 - Perdana, Kurnia Ali Akbar; Yoga, Ika (Universitas Muhammadiyah Surakarta, 2024)
The study aims to examine the factors that affect the stock returns of consumer products businesses listed on the Indonesia Sharia Stock Index for 2019–2023. The findings of several earlier research that looked at stock returns varied. Thus, more study must be done in order to reassess stock returns. A population of 125 consumer goods companies participated in this study. During the five years of research (2019–2023), which involved 195 observations, 13 companies were chosen using the purposive sample technique. The annual report of the sample company, which is available for download from both the company's and the Indonesian Stock Exchange's (IDX) official websites, provided all of the data used in this study. Multiple regression is one of the data analysis methods used in this study. Classical assumption testing is the first step in the data analysis process. Multiple regression analysis follows, and hypothesis testing concludes. According to the research that has been done, MVA, ROE, and NPM all significantly increase stock returns. In the meanwhile, it partially demonstrates that MVA significantly affects stock returns. The stock returns of primary consumption companies in the ISSI index are positively and significantly impacted by the ROE variable. Similarly, the stock returns of primary consumption companies in the ISSI index are positively and significantly impacted by the NPM component.